Custo energético da produção do maracujá amarelo na região de Marília-SP - Furlaneto, Fernanda de Paiva Badiz; Esperancini, Maura Seiko Tsutsui [UNESP]; Bueno, Osmar de Carvalho [UNESP]; Martins, Adriana Novais; Vidal, Anelisa de Aquino (EIA Energy in Agriculture, 2013)
The study evaluated the energy balance of the yellow passion fruit (Passiflora edulis Sims) production system in the region of Marilia-SP. There were analyzed the "inputs" of energy originated from biological, fossil, and industrial sources, and the "output" of energy in the form of fruits produced per unit area, as well as five energy indicators. The phytotechnical indices considered were: planting in February (seedling in tubes), production cycle: 18 months, and yield: 20 t/ha. The input energy totaled 173,707.86 MJ/ha. The most representative items corresponded to industrial indirect energy (38%) and to biological (34%). Chemical fertilizers and pesticides accounted for 65% and 31% of indirect energy industry, respectively. The activity generated 391,800.00 MJ per cycle/ha, and the culture productivity, 0.12 MJ/kg. The efficiency of the culture was 2.26. The net cultural energy totaled 218,092.15 MJ/ha. The energy balance was positive (126,050.23 MJ/ha). Energy efficiency was favorable, with a value of 3.64. The direct power consumption of fossil origin is significant in the system evaluated, but it still allows the production of the yellow passion fruit in an environmentally sustainable way.

O estudo teve como objetivo avaliar energeticamente o principal sistema de produção do maracujá amarelo (Passiflora edulis Sims) na região de Marília-SP. Foram analisadas as "entradas" de energia de origem biológica, fóssil e industrial e a "saída" energética na forma de frutos produzidos por unidade de área, bem como cinco indicadores energéticos. Os índices fitotécnicos considerados foram: plantio no mês de fevereiro (muda em tubete), ciclo de produção: 18 meses, produtividade: 20 t/ha. A entrada energética totalizou 173.707,86 MJ/ha. Os itens mais representativos corresponderam à energia indireta industrial (38%) e biológica (34%). Os adubos químicos e defensivos responderam por 65% e 31% da energia indireta industrial, respectivamente. A atividade gerou, por ciclo/ha, 391.800,00 MJ, sendo a produtividade cultural 0,12 MJ/kg. A eficiência cultural foi de 2,26. A energia cultural líquida totalizou 218.092,15 MJ/ha. O balanço energético foi positivo (126.050,23 MJ/ha). A eficiência energética mostrou-se favorável, apresentando um valor 3,64. Notou-se que o consumo de energia direta de origem fóssil, mesmo que significativo no sistema avaliado, ainda permite a produção do fruto de maneira ambientalmente sustentável.
Energy cost of the yellow passion fruit production inthe region of Marília-SP
Keywords: Passiflora edulis Sims; Yellow passion fruits; Energy balance; Passiflora edulis Sims; Maracujazeiro amarelo; Balanço energético